Low skeletal muscle density is a risk factor for constipation in patients on maintenance dialysis - Li, Mengting; Yin, Qing; Hou, Shimei; Hao, Lirong; Hao, Jianbing; Zhang, Liuping; He, Wei; Xie, Qinglei (Frontiers in Physiology, 2025)
BackgroundConstipation is among the most common gastrointestinal disorders among dialysis patients. Low skeletal muscle density (SMD), a marker of increased intramuscular fat infiltration in muscle, is also among the important characteristics of dialysis patients. This study aimed to assess whether a low SMD is associated with constipation in patients on maintenance dialysis.MethodsA total of 428 dialysis patients from three dialysis centers in our hospital were enrolled in this cross-sectional study. Constipation was assessed according to the Rome IV diagnostic criteria. The SMD was determined via computed tomography (CT) at the first lumbar vertebra level. Univariate and multivariate logistic regression analyses were used to explore the potential effect of SMD on constipation.ResultsThe mean age of all participants was 56.09 (±15.17) years. The percentage of male participants was 42.99%. In accordance with the Rome IV diagnostic criteria, the prevalence of constipation among dialysis patients was 62.62%. We found that compared with that of patients with no constipation, the SMD of patients with constipation was significantly lower [31.70 (±7.33) HU vs. 38.44 (±6.44) HU, P < 0.001]. Decreased SMD was significantly associated with constipation in dialysis patients. The association remained statistically significant even after adjusting for age, dialysis vintage, hemoglobin concentration, serum phosphate concentration and history of diabetes, skeletal muscle index and body mass index. The odds ratios were 0.26 (0.10–0.70), 0.25 (0.08–0.80) and 0.21 (0.05–0.80) for SMD quartile 2, quartile 3 and quartile 4, respectively (reference, quartile 1). Furthermore, the area under the curve (AUC) of the nomogram in the training group was 0.74, whereas that in the test group was 0.76.ConclusionDialysis patients have a high prevalence of constipation. We found that a low SMD is an independent risk factor for constipation. Our findings provide a new perspective on the causes of susceptibility to constipation among dialysis patients.